2005
DOI: 10.1086/432675
|View full text |Cite
|
Sign up to set email alerts
|

Anticorrelated Hard X‐Ray Time Lag in GRS 1915+105: Evidence for a Truncated Accretion Disk

Abstract: Multi-wavelength observations of Galactic black hole candidate sources indicate a close connection between the accretion disk emission and the jet emission. The recent discovery of an anti-correlated time lag between the soft and hard X-rays in Cygnus X-3 (Choudhury & Rao 2004) constrains the geometric picture of the diskjet connection into a truncated accretion disk, the truncation radius being quite close to the black hole. Here we report the detection of similar anti-correlated time lag in the superluminal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 23 publications
(34 reference statements)
10
40
0
Order By: Relevance
“…Examination of the model independent spectra showed that there were minute changes indicating pivoting and marginal pivoting. Similar kind of pivoting features were observed in Cyg X-3, XTE J1550-564 and GRS 1915+105 (Choudhury & Rao 2004, Choudhury et al 2005, Sriram et al 2007). …”
Section: Analysis and Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Examination of the model independent spectra showed that there were minute changes indicating pivoting and marginal pivoting. Similar kind of pivoting features were observed in Cyg X-3, XTE J1550-564 and GRS 1915+105 (Choudhury & Rao 2004, Choudhury et al 2005, Sriram et al 2007). …”
Section: Analysis and Resultssupporting
confidence: 77%
“…Both the sources show a pivoting feature and changes in the spectral parameters during the lags (Choudhury et al 2005, Sriram et al 2007. The lags obtained between soft and hard flux in SPL/VHS state clearly suggest that the accretion disk structure changes, may be because of relative changes in the mass accretion rate.…”
Section: Discussionmentioning
confidence: 82%
“…For Cyg X-3, the anti-correlated hard lags are detected in the hard state, which range from ∼ 620 to ∼ 950 seconds (Choudhury & Rao 2004). The anti-correlated hard lags are detected in the IMS of GRS 1915+105 (Choudhury et al 2005), XTE 1550-564 (Sriram et al 2007) and H1743-322 (Sriram, Agrawal, & Raghurama Rao 2009), which range from ∼ 128 to ∼ 1600 seconds, ∼ 132 to ∼ 376 seconds and ∼ 442 to ∼ 1591 seconds, respectively. From the above results, it is easy to note that the ranges of anti-correlated hard lags detected in different BHXBs are similar.…”
Section: Comparison With Other Xrbsmentioning
confidence: 90%
“…Since then cross-correlation analysis has been widely used for study of the timing properties of XRBs. Tens of seconds to over 1500 seconds anti-correlated time lags were detected in the IMS of other BHXBs that are GRS 1915+105 (Choudhury et al 2005), XTE J1550-564, 4U 1630-47 (Sriram et al 2007), H1743-322 Raghurama Rao 2009) andGX 339-4 (Sriram, Rao, &Choi 2010). Similar kinds of anti-correlated time lags were observed in six other NS LMXBs, including four Z-sources (Cyg X-2 (Lei et al 2008), GX 5-1 (Sriram, Choi, & Rao 2012), XTE J1701-462 (Wang et al 2014) and GX 349+2 (Ding et al 2016)) and two atoll sources (4U 1735-44 (Lei et al 2013) and 4U 1608-52 ), and positive correlated time lags were also observed in them.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the cross correlation function (CCF) gives an insight into the correlation strength of the energy dependence of light curves, which would unhttp://pkas.kas.org veil the various mechanisms involved in the accretion disk. Earlier studies of CCFs between soft and hard energy bands in a few black hole and neutron star sources showed anti-correlated hard/soft delays of a few tens to hundreds of seconds, though most of them were found to be correlated (Choudhury et al, 2005;Sriram et al, 2007;Lei et al, 2008;Sriram et al, 2009;Sriram et al, 2010;Sriram et al, 2012). These studies of CCFs were performed at a high Fourier time scale or correlation time scale of the order of a few hundreds to thousands seconds.…”
Section: Introductionmentioning
confidence: 98%